2020
DOI: 10.3389/fphys.2020.593962
|View full text |Cite
|
Sign up to set email alerts
|

Two Splice Isoforms of Leptinotarsa Ecdysis Triggering Hormone Receptor Have Distinct Roles in Larva-Pupa Transition

Abstract: Insect ecdysis triggering hormone (ETH) receptors (ETHRs) are rhodopsin-like G protein-coupled receptors. Upon binding its ligand ETH, ETHR initiates a precisely programed ecdysis behavior series and physiological events. In Drosophila melanogaster, the ethr gene produces two functionally distinct splicing isoforms, ethra and ethrb. ETH/ETHRA activates eclosion hormone (EH), kinin, crustacean cardioactive peptide (CCAP), and bursicon (burs and pburs) neurons, among others, in a rigid order, to elicit the behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
(99 reference statements)
1
7
0
Order By: Relevance
“…The same method as previously described 34,35 was used to express ds LdRan and ds egfp , derived from a 361‐bp fragment of LdRan and a 414‐bp enhanced green fluorescent protein ( egfp ) gene from Aequorea victoria , using specific primers listed in Table S1. All dsRNAs were generated by Escherichia coli HT115 (DE3) competent cells lacking RNase III following the established method 10,11 . The bacterial solutions (at a dsRNA concentration of about 0.5 μg/mL) were used for the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The same method as previously described 34,35 was used to express ds LdRan and ds egfp , derived from a 361‐bp fragment of LdRan and a 414‐bp enhanced green fluorescent protein ( egfp ) gene from Aequorea victoria , using specific primers listed in Table S1. All dsRNAs were generated by Escherichia coli HT115 (DE3) competent cells lacking RNase III following the established method 10,11 . The bacterial solutions (at a dsRNA concentration of about 0.5 μg/mL) were used for the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…All dsRNAs were generated by Escherichia coli HT115 (DE3) competent cells lacking RNase III following the established method. 10,11 The bacterial solutions (at a dsRNA concentration of about 0.5 μg/mL) were used for the experiment.…”
Section: Preparation Of Dsrnasmentioning
confidence: 99%
See 2 more Smart Citations
“…Since these processes are exclusive to arthropods, homologous proteins are not found in other organisms, making genes from these metabolic and signaling pathways suitable for RNAi molecule development [ 53 ]. Several studies have shown abnormal development in species in which ETH or ETHr genes were knocked down by RNAi [ 54 , 55 , 56 , 57 , 58 ]. Furthermore, our group has previously demonstrated that knockdown of ETHr in CBW larvae leads to lethality and uncompleted metamorphosis [ 59 ].…”
Section: Introductionmentioning
confidence: 99%